Pengaruh Faktor Internal Terhadap Keberhasilan Start-Up Bisnis Di Kota Surabaya - Sri Natasha Br Sitepu (Universitas Airlangga, 2017)
Start-up businesses in Surabaya has developed quite rapidly. The majority of Surabaya city's economy is driven by the industrial sector and the business sector. The successful start-up business in Surabaya is influenced by internal and external factors. Internal factors from the standpoint of companies can be divided into four groups: marketing, human resources, finance, and operations. The object of this study is a start-up business that is / operating in the city of Surabaya. Total sample of 80 respondents. This research uses quantitative methods in the processing of data and information. The aim of research to determine the effect the management of internal factors in the success of a start-up business seen from the perspective of companies. This study uses a quantitative method with multiple regression analysis techniques. The results showed the management of internal factors (marketing, human resources, finance, and operational) at the same time have a positive influence on the success of start-up businesses Surabaya. This study contributes to the entrepreneur in order to optimize the management of internal factors to the success of start-up businesses.